Association between socioeconomic contextual factor, dental care service availability, and prevalence of periodontitis in Brazil: a multilevel analysis - Leonardo Vilar Filgueiras; Fabiana da Silva Cabreira; Luciane Maria Pilotto; Roger Keller Celeste (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2023)
This study aimed to examine the effect of dental care services on periodontitis cases in Brazilian municipalities. The sample comprised 3,426 individuals aged 35-44 years. Moderate to severe periodontitis with clinical attachment loss and probing depth was the dependent variable, both > 3mm. Its exploratory variables were grouped into four categories: (1) individual characteristics; (2) contextual development indicators; (3) health service and structural factors; and (4) dental care use. Data were collected using the SBBrasil 2010 Project, the Brazilian Institute of Geography and Statistics, the Brazilian Information System of Primary and Secondary Care, and the Program to Improve Access and Quality of Dental Specialization Centers (PMAQ-CEO). Multilevel logistic regression was used to assess associations of periodontitis with individual and context variables. Municipalities with > 1 CEO or > 1 of any centers were associated with periodontitis, with OR = 0.97 (95%CI: 0.55-1.71) and OR = 0.41 (95%CI: 0.17-0.97), respectively. Prevalence of periodontitis was more likely in older people, lower education levels, and individuals that sought dental visits for pain/extraction and periodontal treatment. Other dental care services availability were not associated with the prevalence of periodontitis.